Culture: The Unexpected Key to Exemplary Primary Care - Sullivan, Erin E.; Arabadjis, Sophia D.; Alpert, Jessica L.; Ellner, Andrew L. (Journal of Organizational Psychology, 2018)
Health care organizations achieve better outcomes at lower cost where known advances in primary care have been implemented. With few exceptions, primary care in the US has been unsuccessful in implementing these advances. We conducted eight case studies of exemplar primary care organizations to theorize best systems design in adverse conditions; we offer a cross-case analysis. Every study site had culture characterized by 1) trusting, long-term relationships; and 2) power, responsibility, and authority redistribution. Organizational culture may drive exemplary primary care; building cultures with identified traits may improve primary care outcomes and is actionable.